2015
DOI: 10.1038/srep07653
|View full text |Cite
|
Sign up to set email alerts
|

HPV16 early gene E5 specifically reduces miRNA-196a in cervical cancer cells

Abstract: High-risk human papillomavirus (HPV) type 16, which is responsible for greater than 50% of cervical cancer cases, is the most prevalent and lethal HPV type. However, the molecular mechanisms of cervical carcinogenesis remain elusive, particularly the early steps of HPV infection that may transform normal cervical epithelium into a pre-neoplastic state. Here, we report that a group of microRNAs (microRNAs) were aberrantly decreased in HPV16-positive normal cervical tissues, and these groups of microRNAs are fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Cervical cancer (CC) has a high death rate and is the third most common type of cancer worldwide [ 1 ]. It is estimated that over 529,000 people are diagnosed with cervical cancer every year, with most cases occurring in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical cancer (CC) has a high death rate and is the third most common type of cancer worldwide [ 1 ]. It is estimated that over 529,000 people are diagnosed with cervical cancer every year, with most cases occurring in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the efficacy of Z HPV16 E7 affitoxin384, cell viability assay was performed with CCK-8 kit (Dojindo) as described in a previous study with minor modifications 30 . Briefly, SiHa, CaSki, HeLa and A375 cells were plated onto a 96-well plate at 1×10 4 cells per well, followed by treatment with Z HPV16 E7 affitoxin384 at different concentrations (0.1, 0.25, 0.5, 1.0 and 2.0 μM).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that HPV16 E5 specifically down-regulates miR196a upon infection of the human cervix facilitating the transformation of normal cervix cells to cervical carcinoma. 68,69 Further, miR-34a showed also a reduced expression occurring in an early-onset event in the development of HPV associated cervical cancer. The oncoprotein E6 was suggested to reduce miR-34a expression in the p53-dependent pathway during precancerous lesions, although the exact mechanisms remain unclear.…”
Section: Cervical Cancer and Mirnasmentioning
confidence: 99%